2022
DOI: 10.1111/bph.15749
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic‐acid derivative BGP‐15 improves diastolic function in a rabbit model of atherosclerotic cardiomyopathy

Abstract: Background and Purpose The small molecule BGP‐15 has been reported to alleviate symptoms of heart failure and improve muscle function in murine models. Here, we investigated the acute and chronic effects of BGP‐15 in a rabbit model of atherosclerotic cardiomyopathy. Experimental Approach Rabbits were maintained on standard chow (control) or atherogenic diet (hypercholesterolemic) for 16 weeks. BGP‐15 was administered intravenously (once) or orally (for 16 weeks), to assess acute and chronic effects. Cardiac fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Transmitral A wave was also decreased after the treatment, corresponding to our previous findings that BGP-15 has negative tropic effects on the human atria [ 28 ]. Similar outcomes were obtained from the 2-week studies, as BGP-15 treatment did not affect systolic parameters (EF, CO), but improved diastolic function, corresponding to our previous results in different animal models [ 25 , 29 ]. In addition, in the 2-week studies, we found worsened diastolic function (E/A, DecT) and significantly elevated LV mass in the ISO group, in accordance with the literature data [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Transmitral A wave was also decreased after the treatment, corresponding to our previous findings that BGP-15 has negative tropic effects on the human atria [ 28 ]. Similar outcomes were obtained from the 2-week studies, as BGP-15 treatment did not affect systolic parameters (EF, CO), but improved diastolic function, corresponding to our previous results in different animal models [ 25 , 29 ]. In addition, in the 2-week studies, we found worsened diastolic function (E/A, DecT) and significantly elevated LV mass in the ISO group, in accordance with the literature data [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Ca 2+ -transients measured in the presence of BGP-15 tended to decrease when compared to ISO controls, showing that BGP-15 may partly affect Ca 2+ overload in cardiomyocytes. Interestingly, BGP-15 caused an increase in diastolic (and resting) sarcomere length, which might be a result of its actions on titin phosphorylation, which was previously shown by our team [ 29 ].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…3). Increased activity and reduced oxidation of PKGIα led to increase phosphorylation of different myofilament proteins including titin and troponin I, which are known to be significantly hypophosphorylated in HFpEF patients and animal models [31][32][33]50,51,[178][179][180][181][182][183]. In line with that, increasing PKG activity improved deranged titin N2-Bus phosphorylation thereby lowering titin N2-B unique sequence (N2-Bus) bending rigidity and improve passive stiffness [31,50,178,181].…”
Section: Diastolic Dysfunction and Cardiac Stiffnessmentioning
confidence: 58%